Length-weight and length-length relationships for six fish species from Zohreh River, Iran - Yazdan Keivany; Mazaher Zamani-Faradonbe (International Journal of Aquatic Biology, 2017)
The present study reports Length-weight and length-length parameters for six fish species belonging to four families from the Zohreh River. The weight-length relationships were estimated using the equation W= 𝛼Lb. The values of the slope parameter (b) varied between 2.72 and 3.72, with a mean±SD of 3.015±0.18. The values b parameter in the length-weight relationship equations were calculated as 2.72 for Arabibarbus grypus (Heckel, 1843), 2.96 for Capoeta trutta (Heckel, 1843), 2.72 for Garra rufa (Heckel, 1843), 3.25 for Aphanius dispar (Rüppell, 1829), 2.91 for Sillago sihama (Forsskål, 1775) and 3.15 for Glyptothorax silviae Coad, 1981. This study presents the first reference on LWR and LLR for these species in Zohreh River.